Atrophy Masseter Recovery by Electrical Stimulation Mediated M2‐Like Macrophage Polarisation via JAK/PI3K/AKT Pathway - Chuan Wu; Xiuyun Zheng; Qingchun Li; Yi Chen; Wei Liu; Xinyi Song; Quancheng Han; Qunyan Zhang; Chunfeng Fu; Qing Mei; Xiaoyu Liu; Junji Xu; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Atrophy of the masseter muscle can result in an aged facial appearance and diminished chewing function. Electrical stimulation (ES) is known for its ability to facilitate tissue healing and functional recovery, but its precise role in the repair of atrophic masseter muscles remains incompletely understood. Methods We induced masseter muscle atrophy in rats through botulinum toxin (BTX) injection and subsequently treated the animals with or without ES. Single‐nucleus sequencing (sn‐RNA seq) was conducted to analyse the changes in macrophages of masseter muscles between control, BTX and BTX + ES groups. The role and mechanism of macrophage phenotypic transformation in the process of ES promoting the recovery of atrophied masseter muscles were both verified through in vivo and in vitro experiments. Results Our results indicate that ES treatment within defined current parameters significantly ameliorated muscle condition by reducing atrophy‐related gene expression (MuRF1: BTX: 10.15 ± 1.69; BTX + ES: 1.05 ± 0.06; Fbxo32: BTX: 8.62 ± 1.19, BTX + ES: 1.19 ± 0.07, p < 0.0001) and enhancing vascularisation (Vegf positive area: BTX: 6.60 ± 2.87%, BTX + ES: 27.23 ± 1.70%, p < 0.001). Analysis conducted with sn‐RNA seq demonstrated increased infiltration of M1 macrophages during muscle atrophy, with a subsequent transition to M2 macrophages following ES treatment (M1 macrophage portion: Ctrl: 15.2%, BTX: 25.8%, BTX + ES: 14.7%; M2 macrophages: Ctrl: 67.9%, BTX: 46.9%, BTX + ES: 70.5%). Further investigations demonstrated that ES reduced M1 macrophage infiltration (five‐fold lower of CD86+ cell number, BTX: 30 ± 2; BTX + ES: 6 ± 2, p < 0.0001) while increasing M2 macrophage presence (3.3‐fold higher of CD163+cell, BTX: 10 ± 3; BTX + ES: 33 ± 8, p < 0.01), potentially via activation of the PI3K‐Akt pathway (p‐Akt/Akt ratio, BTX:0.58 ± 0.20%; BTX + ES:1.03 ± 0.07%, p < 0.05). Depletion of macrophages using clodronate liposomes reversed the beneficial effects of ES on induced masseter atrophy (MuRF1: BTX + ES: 2.20 ± 0.16; BTX + ES + CL: 12.93 ± 0.98, p < 0.0001), highlighting the involvement of macrophages in the therapeutic process. In vitro studies demonstrated that ES promoted the transition from M1 to M2 macrophages and enhanced proliferation and differentiation of myogenic cells. Conclusions Our findings suggest that ES can enhance masseter muscle tissue repair by modulating macrophage polarisation, offering valuable insights into the potential of ES in noninvasive tissue regeneration strategies for treating masseter muscle atrophy.